The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12020-016-0989-3
|View full text |Cite
|
Sign up to set email alerts
|

Serial post-surgical stimulated and unstimulated highly sensitive thyroglobulin measurements in low- and intermediate-risk papillary thyroid carcinoma patients not receiving radioactive iodine

Abstract: The purpose of this study was to determine the natural temporal trends of serial thyroglobulin (Tg) among low/intermediate-risk PTC patients not receiving radioactive iodine (RAI) using TSH-stimulated Tg (Stim-Tg) and unstimulated highly sensitive Tg (u-hsTg). We prospectively analyzed serial Stim-Tg measurements after total thyroidectomy ± therapeutic central neck dissection among 121 consecutive low/intermediate-risk PTC patients who did not receive RAI, of whom 104 also had serial u-hsTg measurements availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In accordance with Giovanella et al, periodic (serial) highly sensitive, unstimulated thyroglobulin measurements could compensate for this shortcoming, because tumor recurrence is detected early on due to a continuous rise (8). The usefulness of this approach has already been confirmed by other publications (23,24,25).…”
Section: Discussionsupporting
confidence: 52%
“…In accordance with Giovanella et al, periodic (serial) highly sensitive, unstimulated thyroglobulin measurements could compensate for this shortcoming, because tumor recurrence is detected early on due to a continuous rise (8). The usefulness of this approach has already been confirmed by other publications (23,24,25).…”
Section: Discussionsupporting
confidence: 52%
“…Stimulated and unstimulated Tg levels have been available for the last several decades as markers of disease surveillance, and are now utilized to determine post-operative treatment, specifically the need for radioactive iodine or the need for repeat surgical intervention (11). Several studies have shown that undetectable post-operative Tg levels correspond with a low incidence of recurrence, while elevated Tg levels are associated with recurrence (1215).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of highly sensitive Tg (hsTg), whose functional sensitivity is about 0.1 or 0.2 ng/mL, allows for the simplification of the follow-up protocol, avoiding the need for stimulated Tg (stTg). In fact, hsTg proved its equivalence in revealing distant metastases compared with stTg, even in patients without RRA [ 32 , 33 , 34 , 35 ].…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%